2003
DOI: 10.1191/0267659103pf662oa
|View full text |Cite
|
Sign up to set email alerts
|

A rise of MMP-2 and MMP-9 in bronchoalveolar lavage fluid is associated with acute lung injury after cardiopulmonary bypass in a swine model

Abstract: Postoperative acute lung injury (ALI) contributes to the morbidity and mortality following cardiopulmonary bypass (CPB). To determine whether the presence of matrix metalloproteinases (MMPs) is associated with ALI after CPB, MMP-2 and MMP-9 activities in bronchoalveolar lavage fluid (BALF) were compared with parameters indicating impaired gas exchange. In a prospective study, 17 minipigs were subjected to CPB for 60 min. Before and at five and 180 min after CPB, MMP-2 and MMP-9 were assayed in BALF and the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…A pig model of lung injury after cardiopulmonary bypass (CPB) also demonstrated a rise of both MMP-2 and -9 in BAL that correlated with the alveolar-arterial oxygen gradient (PA-a,O 2 ) [24]. However, no other markers of lung injury were used in this study to rule out increased PA-a,O 2 caused by a high ventilation/ perfusion ratio or physiological dead space secondary to suboptimal perfusion on CPB.…”
Section: In Vivo Modelsmentioning
confidence: 86%
“…A pig model of lung injury after cardiopulmonary bypass (CPB) also demonstrated a rise of both MMP-2 and -9 in BAL that correlated with the alveolar-arterial oxygen gradient (PA-a,O 2 ) [24]. However, no other markers of lung injury were used in this study to rule out increased PA-a,O 2 caused by a high ventilation/ perfusion ratio or physiological dead space secondary to suboptimal perfusion on CPB.…”
Section: In Vivo Modelsmentioning
confidence: 86%
“…This has been further supported by demonstration of increases following bleomycin injury in rats [105] and in a pig model of lung injury after cardiopulmonary bypass [106]. In human studies, the results have been more equivocal; one study demonstrated increased levels of MMP-2 and MMP-9, but at lower levels than a matched hospital-acquired pneumonia cohort [107].…”
Section: Pathogenesis Of Ardsmentioning
confidence: 98%
“…Furthermore, increased MMP2 and MMP9 in bronchoalveolar lavage fluid (BALF) have been noted in patients with ARDS (8,28,46). In several experimental models, MMP2 and MMP9 have been implicated in the development of lung injury (7,11,14) while their inhibition attenuated injury (5,14,42,54). Of relevance, a broad-spectrum MMP inhibitor attenuated lung injury caused by high-volume ventilation (14).…”
mentioning
confidence: 99%